Surface mechanical alloying coated zinc carbonyl iron powder absorbent and preparation method thereof
The surface mechanical alloying process of carbonyl iron powder is coated with zinc powder to form a uniform and dense zinc layer, which solves the problem of corrosion of carbonyl iron powder in a high salinity environment, significantly improves its corrosion resistance and electromagnetic wave absorption performance, and reduces production costs and equipment requirements.
Patent Information
- Application Number
- CN202411837512.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
Carbonyl iron powder is prone to corrosion in a high salinity environment, resulting in reduced performance and shortened service life. The existing anti-corrosion measures fail under harsh conditions, and the traditional process costs are high, equipment requirements are high, and the preparation process is cumbersome.
The surface mechanical alloying process of the carbonyl iron powder is coated with zinc powder to form a uniform and dense zinc layer, which uses the cathodic protection effect of zinc to improve corrosion resistance, and optimizes the distribution and density of the zinc layer through ball mill mechanical alloying treatment.
It significantly improves the seawater corrosion resistance and electromagnetic wave absorption performance of carbonyl iron powder, reduces production costs and equipment requirements, simplifies the process flow, and ensures that the material maintains excellent characteristics in extreme environments.
Smart Images

Figure CN119609126A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powder surface treatment, and in particular relates to a surface mechanical alloying coated zinc carbonyl iron powder absorbent and a preparation method thereof. Background Art
[0002] Carbonyl iron powder occupies an important position in the field of absorbing materials due to its excellent magnetic properties and outstanding electromagnetic wave absorption ability, especially in key applications such as radar stealth technology and electromagnetic shielding. However, a major challenge facing this material is the corrosion resistance in high-salinity environments. The high concentration of salt in environments such as the ocean can cause rapid corrosion of carbonyl iron powder, severely weakening its originally excellent performance and significantly reducing its service life. This not only affects the application effect of carbonyl iron powder, but also limits its practicality in scenarios that require extremely high material stability and durability.
[0003] Although traditional anti-corrosion measures such as surface coating or electroplating can provide initial protection, they often fail when exposed to harsh conditions for a long time. For example, the coating may be damaged by physical wear, chemical aging or external impact, causing the protective layer to rupture; the electroplating layer may also gradually peel off or lose its anti-corrosion effectiveness due to mechanical stress, chemical erosion and other factors. Therefore, for application scenarios that require long-term reliability, it is particularly important to explore and develop new long-term anti-corrosion technologies to ensure that carbonyl iron powder can maintain its excellent properties in extreme environments. In response to this demand, researchers are looking for more advanced solutions, including but not limited to the development of new corrosion-resistant materials, the use of nanotechnology to enhance surface protection, and the exploration of other innovative methods to improve the overall durability and stability of carbonyl iron powder.
[0004] Patent A preparation method and application of corrosion-resistant carbonyl iron powder absorber microcapsules with polymer shell (CN118204020A) discloses a carbonyl iron powder absorber microcapsule that can be used to prepare electromagnetic wave stealth materials such as absorbing coatings and resin-based composite materials; however, the durability of the polymer shell may be affected by environmental factors (such as ultraviolet radiation, chemical corrosion, etc.), and may age and crack after long-term use. Patent A corrosion-resistant carbonyl iron electromagnetic absorber with inorganic and organic composite coating and its preparation method and application (CN117819610A) discloses a corrosion-resistant carbonyl iron electromagnetic absorber with a core-shell structure of carbonyl iron metal powder @ inorganic two-dimensional sheet @ polymer organic matter; however, the preparation process of this scheme is too cumbersome, and the requirements for equipment and operation are too high. In addition, in this invention, a composite coating structure composed of inorganic and organic materials is used. However, due to the large difference in the thermal expansion coefficients of these two materials, the expansion or contraction speed of each layer of material is inconsistent during temperature changes, resulting in stress accumulation at the interface. This stress may cause the bonding between the coating layers to be insufficiently strong, and delamination or cracking may gradually occur during long-term use, which not only weakens the protective effect of the coating on the substrate, but may also shorten the service life of the product and have a negative impact on its reliability. Zinc, as a metal with strong electronegativity, can protect the carbonyl iron powder from corrosion by sacrificing itself, that is, extending the service life of the carbonyl iron powder through the principle of cathodic protection. In the prior art, zinc plating is mostly used for corrosion protection, but its application in electromagnetic wave absorbing materials is still challenging. The main problem is how to form a uniform, continuous and dense zinc layer on the surface of fine carbonyl iron powder by a suitable method while maintaining the electromagnetic wave absorption performance of the material. Summary of the invention
[0005] The purpose of the embodiment of the present invention is to provide a surface mechanical alloying coated zinc carbonyl iron powder absorber and a preparation method thereof, so as to solve the problems of high process cost, poor seawater corrosion resistance and poor wave absorbing performance in the prior art.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is a method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent, and the specific process is: firstly, the carbonyl iron powder is surface treated, and the surface treated carbonyl iron powder is coated with zinc powder and then heat treated to obtain the zinc-coated carbonyl iron powder.
[0007] Furthermore, the particle size of the carbonyl iron powder is 20±1 μm, and the average particle size of the zinc powder is 1±0.1 μm; the surface-treated carbonyl iron powder accounts for 85% to 95% of the total mass of the mixed powder; and the zinc powder accounts for 5% to 15% of the total mass of the mixed powder.
[0008] Furthermore, the surface treatment of the carbonyl iron powder is specifically carried out according to the following steps: S101, first disperse the carbonyl iron powder in an organic solvent, perform ultrasonic cleaning at an ultrasonic power of 38-42 W / L for 15-25 min, and then perform water washing at an ultrasonic power of 15-25 W / L for 8-12 min; after the water washing, dry in a vacuum drying oven at a vacuum degree of <133 Pa and a temperature of 80-100°C for 10-12 h; S102. Slowly add the carbonyl iron powder treated with S101 to the mixed solution of acid and pickling corrosion inhibitor; stir for 10-20 min; then filter out the acid solution, wash with water, and dry in a vacuum drying oven at a vacuum degree of <133 Pa and a temperature of 80-100°C for 10-12 h.
[0009] Furthermore, the organic solvent in S101 includes one or more combinations of anhydrous ethanol, isopropanol, and acetone; and the mass volume ratio of the carbonyl iron powder to the organic solvent is 10 g: 45-55 ml.
[0010] Furthermore, the acid solution in S102 includes one of hydrochloric acid, sulfuric acid, and phosphoric acid with a mass concentration of 5% to 10%; the pickling corrosion inhibitor accounts for 0.1% to 1% of the mass of the acid solution; The pickling corrosion inhibitor includes one of an imidazoline pickling corrosion inhibitor, triethanolamine, and an XJ-707 phosphoric acid acidizing corrosion inhibitor.
[0011] Furthermore, the specific process of coating the zinc powder with the carbonyl iron powder after surface treatment is as follows: S201. Add grinding balls to the mixed powder of surface treated carbonyl iron powder and zinc powder, and remove the grinding balls after ball milling at a speed of 100-200 rpm for 4-6 h.
[0012] S202. Add grinding balls to the mixed powder treated in S201, and mill at a speed of 240-400 rpm for 8-12 h, then remove the grinding balls.
[0013] Furthermore, the mass ratio of the mixed powder to the grinding balls in S201 is (5-10):1; the mass ratio of the mixed powder to the grinding balls in S202 is (15-25):1.
[0014] Furthermore, the heat treatment is specifically to place the carbonyl iron powder coated with zinc powder in a vacuum drying oven, and heat treat it at 200-300°C for 1-3 hours at a vacuum degree of <133 Pa; and then naturally cool it to room temperature at a vacuum degree of <133 Pa.
[0015] A surface mechanical alloying coated zinc carbonyl iron powder absorbent prepared by the above method.
[0016] Compared with the prior art, the beneficial effects of the present invention include: 1. The present invention utilizes the cathodic protection effect caused by the higher electronegativity of zinc relative to iron. The present invention provides excellent anti-corrosion performance and is particularly suitable for high-salinity environments. By optimizing ball milling parameters (such as time, rotation speed and ball-to-material ratio), a highly uniform coverage of the zinc layer on the surface of the iron powder is achieved, thereby enhancing the corrosion resistance without sacrificing the electromagnetic properties of the material.
[0017] 2. The present invention ensures that the influence of the zinc layer on the inherent electromagnetic wave absorption characteristics of the iron powder is minimized by carefully adjusting the process conditions, thereby ensuring the high performance of the material in practical applications, solving the problem of insufficient seawater corrosion resistance in the prior art, and improving the electromagnetic wave absorption efficiency by converting spherical carbonyl powder into flakes.
[0018] 3. The mechanical alloying process of the present invention does not require high temperature treatment or power supply and can be carried out at room temperature, which not only simplifies the process flow, but also avoids the generation of high temperature, dust and smoke, creating a safer and cleaner operating environment.
[0019] 4. The mechanical alloying of the present invention realizes alloying between elements of the coating at the atomic level through repeated extrusion deformation, cold welding and crushing, forming uniform, fine and highly phase-dispersed composite particles, and its mechanical properties are superior to those of traditional processes.
[0020] 5. Compared with traditional methods such as electroplating and hot-dip galvanizing, the equipment required by the present invention is relatively simple, with low energy consumption and lower production cost, thus providing a solution that is both economical and high-performance for the preparation of electromagnetic wave absorbing materials.
[0021] In summary, the zinc-coated carbonyl iron powder prepared by the mechanical alloying process in the present invention not only maintains the original electromagnetic wave absorption characteristics, but also greatly improves the corrosion resistance. At the same time, it has the advantages of simple operation, low cost, and environmental friendliness. It effectively solves many challenges existing in the prior art and opens up a new path for the application of electromagnetic wave absorption materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 is a microscopic element distribution diagram of Example 1 of the present invention; Figure 2 is a backscattered electron image of Example 1 of the present invention; Figure 3is a comparison diagram of the microwave absorption performance of the sample obtained in Example 2 of the present invention before and after corrosion; Figure 4 This is a comparison chart of the microwave absorption performance test of the coating prepared with untreated carbonyl iron powder before and after seawater corrosion. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In this embodiment, an anti-corrosion process for an electromagnetic wave absorber is provided, which utilizes the difference in electronegativity of zinc to provide cathodic protection for iron powder, thereby significantly improving the corrosion resistance of the iron powder in a seawater environment and ensuring its electromagnetic wave absorption characteristics; the process is specifically carried out in the following steps: S1. Surface treatment of carbonyl iron powder to remove surface impurities or oxides; S101. Select carbonyl iron powder with an average particle size of 20±1 μm and a purity of 99.5% as a base material for electromagnetic wave absorbing material.
[0026] In this embodiment, the carbonyl iron powder uses a particle size of 20 μm to ensure sufficient specific surface area and reaction activity while avoiding the processing difficulties and cost increase that may be caused by too fine a particle size.
[0027] S102, organic solvent washing: Use organic solvent to soak and stir carbonyl iron powder. Use 45-55 ml organic solvent for 10 g carbonyl iron powder. Use a glass rod to stir the carbonyl iron powder evenly and disperse it in the organic solution. Then use ultrasonic equipment to improve the cleaning effect of carbonyl iron powder in organic solvent to remove grease and organic pollutants on the surface of carbonyl iron powder. The ultrasonic power of ultrasonic equipment is 38-42 W / L, and the ultrasonic cleaning time is 15-25 min. After cleaning the carbonyl iron powder in organic solvent, wash the carbonyl iron powder with water, and then use ultrasonic equipment to improve the cleaning effect of carbonyl iron powder in water. The ultrasonic power of ultrasonic equipment is 15-25 W / L, and the ultrasonic cleaning time is 8-12 min. Remove water-soluble pollutants in carbonyl iron powder to improve the interfacial bonding between carbonyl iron powder and zinc powder. The carbonyl iron powder is then thoroughly dried in a vacuum drying oven with a vacuum degree of <133 Pa, a temperature of 80-100°C, and a drying time of 10-12 h.
[0028] In some specific embodiments, the organic solvent includes one or more combinations of anhydrous ethanol, isopropanol, and acetone.
[0029] S103, pickling: select an acid solution with a mass concentration of 5-10% (including one of hydrochloric acid solution, sulfuric acid solution, and phosphoric acid solution) and pour it into a clean plastic container, then add the pickling corrosion inhibitor to the acid solution at a mass ratio of 0.1%-1% of the acid solution, and then mix it for use. Slowly add the carbonyl iron powder to be pickled into the pickling solution to avoid vigorous stirring to generate a lot of heat and bubbles. During the pickling process, gently stir the solution to promote uniform pickling. Stir for 10-20 minutes to allow impurities and pickling solution to fully react, and use a filter to separate the carbonyl iron powder from the pickling solution. Add the pickled carbonyl iron powder into clean water and rinse it. Then place the rinsed carbonyl iron powder in a vacuum drying oven to thoroughly dry the carbonyl iron powder. The vacuum degree of the vacuum drying oven is <133 Pa, the temperature is 80-100°C, and the drying time is 10-12 h.
[0030] In some specific embodiments, the pickling corrosion inhibitor includes one of an imidazoline pickling corrosion inhibitor, triethanolamine, and an XJ-707 phosphoric acid acidizing corrosion inhibitor.
[0031] In this embodiment, the oxide layer and other impurities on the surface of the carbonyl iron powder are removed by chemical etching, which not only improves the activity of the material surface and promotes the uniform deposition and tight bonding of the subsequent zinc coating, but also enhances the mechanical interlocking effect between the zinc layer and the surface roughness. After this treatment, the corrosion resistance of the carbonyl iron powder is significantly improved, thereby showing better stability in harsh environments. If the residual acid and reaction products generated during the pickling process of this embodiment are not completely removed, they may cause secondary corrosion to the material or interfere with subsequent processes. Therefore, they must be removed through sufficient water washing steps, and the material must be completely dried to avoid any potential negative effects.
[0032] S2, ball milling mechanical alloying treatment: zinc powder with an average particle size of 1±0.1 μm and a purity of 99.9% is selected as the coating material, the carbonyl iron powder after surface treatment accounts for 85%~95% of the total mass of the mixed powder; zinc powder accounts for 5%~15% of the total mass of the mixed powder, the pretreated carbonyl iron powder is mixed with zinc powder, and a carbonyl iron / zinc mixed powder with an iron / zinc alloying layer is first prepared by low-energy ball milling, so that the zinc powder is evenly attached to the surface of the carbonyl iron powder; then the carbonyl iron powder attached with zinc powder is flaked by high-energy ball milling to prepare a flaked carbonyl iron / zinc mixed powder. In this embodiment, high-energy ball milling can cause the carbonyl iron powder to undergo significant microstructural changes by applying severe impact, friction and plastic deformation to the powder particles. Specifically, this treatment can transform the original powder into a flake-like structure with specific geometric characteristics: its thickness ranges from approximately 3 to 5 microns, its lateral dimensions are approximately 30 to 50 microns, and it presents a morphology with an aspect ratio of 10 to 15:1. According to the Snoek limit theory, the wave absorption efficiency of ferromagnetic materials is limited by intrinsic physical limitations, which restricts further performance improvements. However, by flattening the material, its microscopic geometric properties can be effectively changed, thereby increasing the magnetic permeability. This change helps to break through the constraints of the traditional Snoek limit on material performance, thereby achieving significant improvements and optimization in the wave absorption efficiency of ferromagnetic materials. This process not only enhances the material's ability to absorb electromagnetic waves, but also expands its potential in high-frequency applications.
[0033] This embodiment uses zinc powder with an average particle size of 1 micron, so that it can form a dense protective layer on the surface of the carbonyl iron powder, effectively isolating the air and seawater, thereby improving its corrosion resistance. Moreover, the 1-micron zinc powder can better form a good bonding force with the surface of the 20-micron carbonyl iron powder. In addition, the 1-micron zinc powder is easier to achieve uniform coating of the carbonyl iron powder, avoiding the situation where the local thickness is too thick or too thin, and the uniform coating layer can provide better corrosion resistance and more stable performance. Zinc is an active metal that can form a galvanic effect with iron, thereby protecting the iron from corrosion. However, the addition of zinc can change the electromagnetic properties of the carbonyl iron powder, such as magnetic permeability and dielectric constant.
[0034] Zinc has a low melting point and low hardness. Excessive addition of zinc may affect the thermal stability of the absorbing material, the magnetic properties of the material, the hardness and wear resistance of the material. A higher proportion of zinc can provide better corrosion resistance, but it will also affect other properties of the carbonyl iron powder, such as magnetic properties and absorbing properties. A lower proportion of zinc will result in limited effect in improving the corrosion resistance of the carbonyl iron powder. Therefore, an appropriate zinc addition ratio can improve the application potential of the material in a high temperature environment without reducing the absorbing performance of the material too much. Further, when the proportion of zinc is high, a thicker and denser zinc layer can be formed on the surface of the carbonyl iron powder, effectively blocking the invasion of the corrosive medium and significantly improving the corrosion resistance. However, it will reduce the magnetic properties such as the saturation magnetization of the carbonyl iron powder, because too much non-magnetic zinc will affect the overall magnetic properties, which may cause the overall absorbing performance of the carbon-based iron powder to decrease. At the same time, when the proportion of zinc is low, the magnetic properties of the carbonyl iron powder will be less affected, but the corrosion resistance may not be obvious, and the protective effect of zinc cannot be fully exerted. In addition, too low a proportion of zinc powder makes it difficult to form an effective anti-corrosion layer, resulting in rapid corrosion of the iron powder in a seawater environment. In this embodiment, the ratio of zinc powder should be at least 5% (ie, the minimum ratio of iron powder to zinc powder is 95:5) to ensure a basic anti-corrosion effect.
[0035] S201. Mix the carbonyl iron powder and zinc powder by low-energy ball milling so that the zinc powder is evenly attached to the surface of the carbonyl iron powder. The mass ratio of the grinding balls to the carbonyl iron / zinc powder mixture is 5:1-10:1. Mill at a speed of 100-200 rpm for 4-6 h, then remove the grinding balls.
[0036] In this embodiment, the low-energy ball milling process should not be shortened by increasing the rotation speed, because increasing the ball milling speed will cause the abrasive to adhere significantly to the inner wall of the ball mill, thereby affecting the ideal dispersion effect. The ball milling at this stage should be continued until the zinc powder and the carbonyl iron powder are completely and evenly mixed to ensure that there is no local aggregation of zinc powder or carbonyl iron powder, that is, to achieve uniform coating of the surface of the carbonyl iron powder by zinc powder.
[0037] In this embodiment, the spherical carbonyl iron powder is converted into flakes through ball milling. The transformation from spherical to flake increases the effective specific surface area and interface polarization effect of the material, thereby enhancing the multiple reflection and scattering of electromagnetic waves inside it, thereby significantly improving the electromagnetic wave absorption efficiency. In addition, the flake structure in this embodiment helps to build a more compact filling structure, which can form a more effective conductive network in the application of composite materials, further promoting the dissipation of electromagnetic energy.
[0038] S202, high-energy ball milling to achieve mechanical alloying of carbonyl iron and zinc, at the same time, to densify the zinc coating, the ball mass ratio of grinding balls to carbonyl iron / zinc powder mixture is 15:1~25:1, and the ball milling is carried out at a speed of 240~400 rpm for 8~12 h.
[0039] In this embodiment, the carbonyl iron powder and the zinc powder are fully mixed by low-energy ball milling process, and the zinc powder particles are evenly dispersed and tightly attached to the surface of the carbonyl iron powder under the action of mechanical force to form a dense zinc coating layer. Subsequently, the composite powder is further refined by high-energy ball milling to optimize the particle size distribution, thereby enhancing the density and uniformity of the coating layer.
[0040] This embodiment uses a mechanical alloying process to generate a zinc coating on the surface of the carbonyl iron powder particles, and the zinc coating is formed by physical mechanisms such as fracture and cold welding of the metal powder particles during ball milling. This physical bonding method promotes the close mechanical engagement between the zinc coating and the carbonyl iron powder matrix, thereby enhancing the interface bonding strength. During the mechanical alloying process, the metal powder particles undergo continuous refinement and plastic deformation, and these deformed particles can be more effectively embedded in the tiny depressions or defects on the surface of the carbonyl iron powder matrix, thereby increasing the contact area and interaction force between the two. In addition, the mechanical alloying process may also be accompanied by diffusion and alloying reactions, further strengthening the bonding between the zinc coating and the carbonyl iron powder matrix. The zinc coating formed by mechanical alloying in this embodiment generally exhibits higher uniformity and density. In contrast, although chemical plating and electroplating techniques can also form a coating on the carbonyl iron powder matrix through chemical reactions and provide a certain bonding strength, their effects are often affected by multiple factors such as the composition of the plating solution and the electroplating conditions, resulting in a relatively weak final bonding strength. The mechanical alloying method of this embodiment is superior to the chemical plating or electroplating method in terms of bonding strength. In addition, in order to further optimize the coating formation process, this embodiment controls the coating thickness and uniformity by finely adjusting key process parameters such as ball milling time, rotation speed, raw material mass ratio, and ball milling medium during the mechanical alloying process; the optimization of these parameters not only helps to improve the uniformity and density of the coating, but also significantly enhances the bonding strength between the coating and the substrate material.
[0041] The coating thickness is mainly controlled by controlling the particle size and mass ratio of the two.
[0042] The uniformity of the coating is mainly controlled by controlling the parameters of the ball milling process.
[0043] S3. Heat-treating the mixed powder to enhance the adhesion and corrosion resistance of the zinc layer.
[0044] S301. In order to improve the bonding strength and corrosion resistance of the zinc layer and the carbonyl iron powder matrix, the dried zinc-coated carbonyl iron powder is heat-treated in a vacuum drying oven. The vacuum degree of the vacuum drying oven is <133 Pa, the heat treatment temperature is 200-300°C, and the time is 1-3 h. After the heat treatment is completed, the composite powder is allowed to cool naturally to room temperature in a vacuum environment.
[0045] S302. Soak the prepared zinc-coated carbonyl iron powder in a prepared artificial seawater solution for 96 hours to test the seawater corrosion resistance of the coated carbonyl iron powder, wherein the content of NaCl in the artificial seawater solution is 25 g / L.
[0046] The heat treatment process in the post-treatment of this embodiment has a significant impact on the microstructure and performance of the carbonyl iron powder. Specifically, within the heat treatment temperature range below 300°C, the micromorphology of the carbonyl iron powder remains unchanged, but its crystallinity can be improved and its coercive force can be reduced. As the temperature increases, the diffusion and penetration rate of zinc atoms on the surface of the iron powder accelerates, which helps to form a denser and more uniform zinc coating layer, thereby enhancing the interface bonding strength and corrosion resistance. However, if the heat treatment temperature is too high, it may cause excessive oxidation of the zinc layer or induce an adverse phase change in the carbonyl iron powder matrix, thereby destroying its original microstructure and electromagnetic properties.
[0047] In some specific embodiments, the temperature range of the heat treatment is set to between 200°C and 300°C. The selection of this temperature range is based on the physical and chemical properties between zinc and iron, and is intended to avoid adverse effects on material properties due to excessively high temperatures. Within this temperature range, the zinc layer can achieve good adhesion without damaging the electromagnetic wave absorption performance of the carbonyl iron powder matrix. The heat treatment time needs to be long enough to ensure sufficient physical and chemical reactions between the zinc layer and the carbonyl iron powder matrix, thereby enhancing the interfacial bonding force. However, if the heat treatment time is too long, it may cause embrittlement in the interface area or generate too much intermediate phase, which in turn weakens the bonding strength and corrosion resistance.
[0048] S4. Conduct corrosion resistance test and electromagnetic wave absorption test on zinc-coated carbonyl iron powder.
[0049] Example 1 S1. Preprocessing S101. Select carbonyl iron powder with an average particle size of 20 microns and a purity of 99.5% as the base material of the electromagnetic wave absorbing material.
[0050] S102. Soak and stir the carbonyl iron powder in anhydrous ethanol. Use 50 ml of organic solvent for every 10 g of carbonyl iron powder. Use a glass rod to stir the carbonyl iron powder evenly and disperse it in the organic solution. Then use an ultrasonic device to improve the cleaning effect of the carbonyl iron powder in the organic solvent to remove grease and organic pollutants on the surface of the carbonyl iron powder. The ultrasonic power of the ultrasonic device is 40 W / L, and the ultrasonic cleaning time is 20 min. After cleaning the carbonyl iron powder in the organic solvent, wash the carbonyl iron powder with water. Use 20 ml of deionized water for 10 g of carbonyl iron powder. Then use an ultrasonic device to improve the cleaning effect of the carbonyl iron powder in water. The ultrasonic power of the ultrasonic device is 20 W / L, and the ultrasonic cleaning time is 10 min. Remove the water-soluble pollutants in the carbonyl iron powder to improve the interfacial bonding between the carbonyl iron powder and the zinc powder. Then, thoroughly dry the carbonyl iron powder in a vacuum drying oven. The vacuum degree of the vacuum drying oven is <133 Pa, the temperature is 90°C, and the drying time is 11 h.
[0051] S103. Pour a 15% hydrochloric acid solution into a clean plastic container, add an imidazoline pickling corrosion inhibitor to the hydrochloric acid solution at a ratio of 0.1%, and then mix well for use. Slowly add the carbonyl iron powder to be pickled into the pickling solution to avoid vigorous stirring to generate a lot of heat and bubbles. During the pickling process, gently stir the solution to promote uniform pickling. Stir for 15 minutes to allow the impurities and the pickling solution to fully react, and use a filter to separate the carbonyl iron powder from the pickling solution. Add the pickled carbonyl iron powder into clean water and rinse. Then place the rinsed carbonyl iron powder in a vacuum drying oven to thoroughly dry the carbonyl iron powder. The vacuum degree of the vacuum drying oven is <133 Pa, the temperature is 90°C, and the drying time is 11 h.
[0052] S2. Ball milling mechanical alloying treatment S201, 85 g of pretreated carbonyl iron powder and 15 g of zinc powder with an average particle size of 1 micron and a purity of 99.9% are used as coating materials in a weight ratio of 85:15; then the carbonyl iron powder and the zinc powder mixed powder are mixed by low-energy ball milling so that the zinc powder is evenly attached to the surface of the carbonyl iron powder, the mass ratio of the grinding ball to the carbonyl iron / zinc powder mixed powder is 5:1, and the ball milling is carried out at a speed of 100 rpm for 4 h; S202, high energy ball milling to achieve mechanical alloying of iron and zinc, and at the same time, densify the zinc layer, the mass ratio of grinding balls to carbonyl iron / zinc powder mixture is 15:1, and the ball milling is carried out at a speed of 240 rpm for 8 hours; S3, post-processing The dried zinc-coated carbonyl iron powder was heat treated in a vacuum drying oven with a vacuum degree of <133 Pa, a heat treatment temperature of 200°C, and a time of 3 hours. After the heat treatment was completed, the composite powder was allowed to cool naturally to room temperature in a vacuum environment.
[0053] Example 2 S1. Preprocessing S101. Select carbonyl iron powder with an average particle size of 20 microns and a purity of 99.5% as the base material of the electromagnetic wave absorbing material.
[0054] S102. Soak and stir the carbonyl iron powder in isopropanol. Use 55 ml of organic solvent for every 10 g of carbonyl iron powder. Use a glass rod to stir the carbonyl iron powder evenly and disperse it in the organic solution. Then use an ultrasonic device to improve the cleaning effect of the carbonyl iron powder in the organic solvent to remove grease and organic pollutants on the surface of the carbonyl iron powder. The ultrasonic power of the ultrasonic device is 42 W / L, and the ultrasonic cleaning time is 25 min. After cleaning the carbonyl iron powder in the organic solvent, wash the carbonyl iron powder with water. Use 20 ml of deionized water for 10 g of carbonyl iron powder. Then use an ultrasonic device to improve the cleaning effect of the carbonyl iron powder in water. The ultrasonic power of the ultrasonic device is 25 W / L, and the ultrasonic cleaning time is 12 min. Remove the water-soluble pollutants in the carbonyl iron powder to improve the interfacial bonding between the carbonyl iron powder and the zinc powder. Then, thoroughly dry the carbonyl iron powder in a vacuum drying oven. The vacuum degree of the vacuum drying oven is <133 Pa, the temperature is 100°C, and the drying time is 12 h.
[0055] S103. Pour a sulfuric acid solution with a mass concentration of 7.5% into a clean plastic container, then add triethanolamine to the sulfuric acid solution at a ratio of 0.5%, and then mix well for use. Slowly add the carbonyl iron powder to be pickled into the pickling solution to avoid vigorous stirring to generate a lot of heat and bubbles. During the pickling process, gently stir the solution to promote uniform pickling. Stir for 20 minutes to allow the impurities and the pickling solution to fully react, and use a filter to separate the carbonyl iron powder from the pickling solution. Add the pickled carbonyl iron powder into clean water for rinsing. Then place the rinsed carbonyl iron powder in a vacuum drying oven to thoroughly dry the carbonyl iron powder. The vacuum degree of the vacuum drying oven is <133 Pa, the temperature is 90°C, and the drying time is 12 h.
[0056] S2. Ball milling mechanical alloying treatment S201, 90 g of pretreated carbonyl iron powder and 10 g of zinc powder with an average particle size of 1 micron and a purity of 99.9% are used as coating materials in a weight ratio of 90:10, and then the carbonyl iron powder and the zinc powder are mixed by low-energy ball milling so that the zinc powder is evenly attached to the surface of the carbonyl iron powder, the mass ratio of the grinding ball to the carbonyl iron / zinc powder mixture is 7.5:1, and the ball milling is carried out at a speed of 150 rpm for 5 hours; S202, high energy ball milling to achieve mechanical alloying of iron and zinc, at the same time, to densify the zinc layer, the mass ratio of grinding balls to carbonyl iron / zinc powder mixture is 20:1, and the ball milling is carried out at a speed of 320 rpm for 10 hours.
[0057] S3 Post-Processing The dried zinc-coated carbonyl iron powder was heat treated in a vacuum drying oven with a vacuum degree of <133 Pa, a heat treatment temperature of 250°C, and a time of 2 hours. After the heat treatment was completed, the composite powder was allowed to cool naturally to room temperature in a vacuum environment.
[0058] Example 3 S1. Preprocessing S101. Select carbonyl iron powder with an average particle size of 20 microns and a purity of 99.5% as the base material of the electromagnetic wave absorbing material.
[0059] S102. Soak and stir the carbonyl iron powder in acetone. Use 45 ml of organic solvent for 10 g of carbonyl iron powder. Use a glass rod to stir the carbonyl iron powder evenly and disperse it in the organic solution. Then use ultrasonic equipment to improve the cleaning effect of the carbonyl iron powder in the organic solvent to remove grease and organic pollutants on the surface of the carbonyl iron powder. The ultrasonic power of the ultrasonic equipment is 38 W / L, and the ultrasonic cleaning time is 20 min. After cleaning the carbonyl iron powder in the organic solvent, wash the carbonyl iron powder with water. Use 20 ml of deionized water for 10 g of carbonyl iron powder. Then use ultrasonic equipment to improve the cleaning effect of the carbonyl iron powder in water. The ultrasonic power of the ultrasonic equipment is 15 W / L, and the ultrasonic cleaning time is 10 min. Remove the water-soluble pollutants in the carbonyl iron powder to improve the interfacial bonding between the carbonyl iron powder and the zinc powder. Then, thoroughly dry the carbonyl iron powder in a vacuum drying oven. The vacuum degree of the vacuum drying oven is <133 Pa, the temperature is 80°C, and the drying time is 10 h.
[0060] S103. Pour a 5% phosphoric acid solution into a clean plastic container, add XJ-707 phosphoric acid corrosion inhibitor to the phosphoric acid solution at a ratio of 1%, and then mix well for use. Slowly add the carbonyl iron powder to be pickled into the pickling solution to avoid vigorous stirring to generate a lot of heat and bubbles. During the pickling process, gently stir the solution to promote uniform pickling. Stir for 10 minutes to allow the impurities and the pickling solution to fully react, and use a filter to separate the carbonyl iron powder from the pickling solution. Add the pickled carbonyl iron powder into clean water and rinse. Then place the rinsed carbonyl iron powder in a vacuum drying oven to thoroughly dry the carbonyl iron powder. The vacuum degree of the vacuum drying oven is <133 Pa, the temperature is 80°C, and the drying time is 10 h.
[0061] S2. Ball milling mechanical alloying treatment S201, 95g of surface-treated carbonyl iron powder and 5g of zinc powder with an average particle size of 1 micron and a purity of 99.9% are mixed as coating materials in a weight ratio of 95:5; then the carbonyl iron powder and the zinc powder are mixed by low-energy ball milling so that the zinc powder is evenly attached to the surface of the carbonyl iron powder, the mass ratio of the grinding ball to the carbonyl iron / zinc powder mixture is 10:1, and the ball milling is carried out at a speed of 200 rpm for 6 hours; S202, high energy ball milling to achieve mechanical alloying of iron and zinc, and at the same time, to densify the zinc layer, the mass ratio of grinding balls to carbonyl iron / zinc powder mixture is 25:1, and the ball milling is carried out at a speed of 400 rpm for 12 hours.
[0062] S3, post-processing The dried zinc-coated carbonyl iron powder was heat treated in a vacuum drying oven with a vacuum degree of <133 Pa, a heat treatment temperature of 300°C, and a time of 1 hour. After the heat treatment was completed, the composite powder was allowed to cool naturally to room temperature in a vacuum environment.
[0063] The comparison of the effective absorption bandwidths of the example of this embodiment and the comparative example of carbonyl iron powder without zinc coating before and after immersion in artificial seawater is shown in Table 1. It can be seen that the absorbing coating prepared from the carbonyl iron powder treated by this embodiment can still maintain good absorbing performance after immersion in seawater. In particular, the effective absorption bandwidth of the sample obtained in Example 2 is only reduced by 5.9% after immersion in artificial seawater, while the effective absorption bandwidth of the sample obtained from the comparative example of pure carbonyl iron powder without zinc coating is reduced by 60% after immersion in artificial seawater.
[0064] Example 4 The organic solvent in S101 is a mixture of isopropanol and acetone in a mass ratio of 1:1, and the remaining steps are the same as those in Example 2.
[0065] Example 5 The organic solvent in S101 is a mixture of anhydrous ethanol, isopropanol and acetone in a mass ratio of 1:1:1, and the remaining steps are the same as those in Example 2.
[0066] Comparative Example 1 S2 is not performed, and the carbonyl iron powder pretreated by S1 is directly post-treated. The remaining steps are the same as those in Example 2.
[0067] Comparative Example 2 S1 is not performed, and the processes of S2 to S3 are performed using the carbonyl iron powder that has not been pretreated. The remaining steps are the same as those in Example 2.
[0068] Comparative Example 3 No post-processing of S3 is performed, and the remaining steps are the same as those in Example 2.
[0069] Comparative Example 4 In S2, only S202 high-energy ball milling is performed to achieve mechanical alloying of carbonyl iron powder and zinc, and the remaining steps are the same as those in Example 2.
[0070] Comparative Example 5 The high-energy ball milling process of S202 is not performed in S2, and the remaining steps are the same as those in Example 2.
[0071] Example 6 In S202, high energy ball milling is performed at 720 rpm, and the remaining steps are the same as those in Implementation 2.
[0072] The performance comparison of the absorbing materials prepared in the examples and comparative examples and the chemically galvanized absorbing materials before and after being immersed in artificial seawater is shown in Table 1: Table 1 Comparison of the microwave absorbing properties of the microwave absorbing coatings obtained in different embodiments and comparative examples before and after immersion in artificial seawater The key point of the embodiment of the present invention is to explore the process of mechanical alloying and zinc coating on the surface of carbonyl iron powder with excellent corrosion resistance and microwave absorption performance. Figure 1 , Figure 2 , a uniform and dense zinc layer is successfully formed on the surface of the carbonyl iron powder through the process of this embodiment. Figure 3 The microwave absorption performance test comparison of the coating prepared for the sample of Example 2 before and after seawater corrosion shows that the microwave absorption performance of the zinc-coated carbonyl iron powder sample is almost unchanged before and after corrosion, and the effective absorption bandwidth is only reduced from 6.4 GHz to 6.2 GHz, a decrease of only 3.13%. Figure 4 The comparison of the microwave absorption performance of the coating prepared by untreated carbonyl iron powder before and after seawater corrosion shows that the effective absorption bandwidth of the untreated carbonyl iron powder is reduced to 0 after seawater corrosion. Figure 3 and Figure 4By comparison, it can be seen that the carbonyl iron powder prepared by the present invention has excellent corrosion resistance. This shows that the zinc coating layer prepared on the surface of the carbonyl iron powder by mechanical alloying not only significantly improves the seawater corrosion resistance of the carbonyl iron powder, but also maintains its excellent absorption characteristics within the electromagnetic wave frequency band. This more clearly shows that the ball milling mechanical alloying process proves its application potential in the preparation of electromagnetic wave absorbing materials in complex environments.
[0073] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent, characterized in that: The specific process is: firstly, the carbonyl iron powder is surface treated, and then the surface treated carbonyl iron powder is coated with zinc powder and then heat treated to obtain zinc-coated carbonyl iron powder.
2. The method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent according to claim 1, characterized in that: The particle size of the carbonyl iron powder is 20±1 μm, and the average particle size of the zinc powder is 1±0.1 μm; the surface-treated carbonyl iron powder accounts for 85% to 95% of the total mass of the mixed powder; and the zinc powder accounts for 5% to 15% of the total mass of the mixed powder.
3. The method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent according to claim 1, characterized in that: The surface treatment of carbonyl iron powder is carried out according to the following steps: S101, first disperse the carbonyl iron powder in an organic solvent, perform ultrasonic cleaning at an ultrasonic power of 38-42 W / L for 15-25 min, and then perform water washing at an ultrasonic power of 15-25 W / L for 8-12 min; after the water washing, dry in a vacuum drying oven at a vacuum degree of <133 Pa and a temperature of 80-100°C for 10-12 h; S102. Slowly add the carbonyl iron powder treated with S101 to the mixed solution of acid and pickling corrosion inhibitor; stir for 10-20 min; then filter out the acid solution, wash with water, and dry in a vacuum drying oven at a vacuum degree of <133 Pa and a temperature of 80-100°C for 10-12 h.
4. The method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent according to claim 3, characterized in that: The organic solvent in S101 includes one or more combinations of anhydrous ethanol, isopropanol, and acetone; the mass volume ratio of the carbonyl iron powder to the organic solvent is 10 g: 45-55 ml.
5. The method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent according to claim 3, characterized in that: The acid solution in S102 includes one of hydrochloric acid, sulfuric acid and phosphoric acid with a mass concentration of 5% to 10%; the pickling corrosion inhibitor accounts for 0.1% to 1% of the mass of the acid solution; The pickling corrosion inhibitor includes one of an imidazoline pickling corrosion inhibitor, triethanolamine, and an XJ-707 phosphoric acid acidizing corrosion inhibitor.
6. The method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent according to claim 1, characterized in that: The specific process of coating zinc powder with carbonyl iron powder after surface treatment is as follows: S201, adding grinding balls to the mixed powder of the surface-treated carbonyl iron powder and zinc powder, and milling at a speed of 100-200 rpm for 4-6 h, and then taking out the grinding balls; S202. Add grinding balls to the mixed powder treated in S201, and mill at a speed of 240-400 rpm for 8-12 h, then remove the grinding balls.
7. The method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent according to claim 6, characterized in that: The mass ratio of the mixed powder to the grinding balls in S201 is (5-10):1; the mass ratio of the mixed powder to the grinding balls in S202 is (15-25):
1.
8. The method for preparing a surface mechanical alloying coated zinc carbonyl iron powder absorbent according to claim 1, characterized in that: The heat treatment specifically comprises placing the carbonyl iron powder coated with zinc powder in a vacuum drying oven, and heat treating the powder at 200-300° C. for 1-3 h at a vacuum degree of <133 Pa; and then naturally cooling the powder to room temperature at a vacuum degree of <133 Pa.
9. A surface mechanical alloying coated zinc carbonyl iron powder absorbent, characterized in that: Prepared according to any one of claims 1 to 8.
Citation Information
Patent Citations
Inorganic-organic composite coated corrosion-resistant carbonyl iron electromagnetic wave-absorbing agent as well as preparation method and application thereof
CN117819610A
Preparation method and application of corrosion-resistant carbonyl iron powder wave-absorbing agent microcapsule with polymer shell layer
CN118204020A
Cited By
High-entropy ceramic wave-absorbing material and design method and preparation method thereof
CN121168022A